Non-invasive real-time biopsy of intracranial lesions using short time expanded circulating tumor cells on glass slide: report of two cases. Issue 1 (December 2016) - Malara, N.; Guzzi, G.; Mignogna, C.; Trunzo, V.; Camastra, C.; Torre, A.; Di Vito, A.; Lavecchia, A.; Gliozzi, M.; Ceccotti, C.; Volpentesta, G.; Lavano, A.; et al.
Abstract Background Circulating Tumor Cells (CTCs) are promising biomarkers for monitoring solid cancer and were used to monitor brain tumors. Here we report two cases in which, for the first time, CTCs were used in cytological diagnostic evaluation to discriminate a space-occupying lesion of the brain. Case presentation Two cases of focal intracranial lesions, unclassified for diagnosis, untreated and apparently symptomatic, were examined after high-contrast resolution Magnetic Resonance Imaging and/or Computed Tomography scans. CTCs were seeded on chamber slides and short-time expanded under the optimized conditions as we previously reported. The first case was a focal lesion localized in the parietal-occipital area in a 67-year-old woman. The second case was a 31-year-old man with an expansive intracerebral lesion localized in the left peri-trigonal area. Both patients underwent excisional biopsy. Histopathological evaluation of the biopsy confirmed the previous cytological diagnoses, and the analysis of the clinical outcomes retrospectively validated both diagnoses. Conclusions The cases here reported illustrate the potential for using expanded CTCs as non-invasive, real-time biopsy. Moreover, non-invasive real-time biopsy can represent an alternative diagnostic tool to be used when a functional area of the brain is at risk of injury from excisional biopsy procedures.